Global extremism: causes & remedy - Abdul Razak, Mohd Abbas; Mustapha, Maziah (2017)
This presentation examines on extremism and act of terror committed at the global level. Since extremism is an age-old phenomenon that existed all throughout in the history of mankind, the presentation will focus on the many forms of extremism that happen during this modern age of globalization and telecommunication. The crux of the presentation will focus on the root causes of extremism and how to remedy the ever increasing rate of terror attacks that happens all over the world. The researchers have also highlighted that it is unfair to associate extremism carried out by people to their religions. This sort of an unfair judgment has been done in the case of a Muslim to Islam, while the non-Muslim is associated to mental illness. Last but not least, the researchers call for a concerted effort from all, regardless race and religion to join force to eradicate extremism and make this world a safe place for all to live.